Produktivitas Ayam Broiler pada Kandang Closed Housed di Peternakan Setiris Kecamatan Maro Sebo Kabupaten Muaro Jambi: Productivity of Broiler Chickens in Closed House Cages at Setiris Farm, Maro Sebo District, Muaro Jambi Regency - Risna, Yayuk Kurnia; Pasarela, Gea Riski; Yusrizal, Yusrizal; Suparjo, Suparjo; Tanti, Ariyani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Housing is a crucial aspect of broiler chicken farming, as comfortable housing conditions significantly impact livestock productivity and profitability. One widely used type of housing is the closed house housing system, designed to limit biological contact between the chickens and the external environment, thereby reducing stress. This housing system offers advantages such as controlled air circulation via automatic panels, protecting the chickens from extreme temperature changes outside the cage, increasing livestock productivity, reducing the risk of disease entry, and facilitating temperature and humidity regulation within the cage. Purpose: determine the production performance of broiler chickens in closed house cages at the Setiris Village farm, Maro Sebo District, Muaro Jambi Regency. Methods: The study was conducted in a closed house in Setiris Village, Maro Sebo District, Muaro Jambi Regency, with a capacity of 21,000 Ross strain chickens. This study used an observational method with a farm performance recording approach, analyzed quantitatively and descriptively. The study was conducted based on direct observation of broiler production performance under actual field conditions without any special treatment. Results: Feed consumption increased with age, with an average of 971 g/bird/week, body weight gain reaching 600 g/bird/week, and an average feed conversion ratio (FCR) of 1.36, indicating optimal feed efficiency. The mortality rate was 2.2%, still within normal limits, and the Performance Index (PI) was 544.55, which is considered very good. Based on these results, the production performance of broiler chickens raised in closed-house cages is considered very good. Conclusion: These results indicate that the management of maintenance, feed, and closed house cage systems has been effective and supports optimal growth of broiler chickens in tropical climate conditions.